Evaluation of Age Related Changes Associated with Exposure of Wistar Rats to Dichlorvor on some Haematological Parameters - S.F. Ige; M.A. Seriki; B.S. Olateju; V.A. Oladipupo (Journal of Applied Sciences and Environmental Management, 2021)
Different studies proved that exposure over prolonged periods to pesticides increase the likelihood of developing adverse effects. 2,2-dichlorovinyl dimethyl phosphate (DDVP) is a predominant pesticide used in controlling insects. Therefore this study was aimed to investigate the age related changes in hematological indices of animals exposed to DDVP. Thirty healthy male Wistar rats were used in this study. Animals were grouped into three major groups of ten animals each. Group one animals served as young group (5 - 6 weeks) while group two and three was the middle-aged (2 months) and old groups (3-4 months) respectively. All the groups were subdivided into control and DDVP group with five animals in each subgroup. The DDVP groups were exposed to DDVP for five weeks. At the end of fifth week, they were euthanized with blood collected through cardiac puncture, hematological indices were analysed with auto hematological analyzer.Exposure to DDVP significantly increased white blood cell counts and basophiles in old group. Platelets count and plateletcrit (PCT) were significantly decreased in young animals that were exposed to DDVP while platelet distribution width (PDW) and Mean platelets volume (MPV) were not significantly different across the groups. Red blood cells count, Hematocrit, Hemoglobin concentration, Mean cell volume, Mean cell hemoglobin and Mean cell hemoglobin concentration also show no significant difference across groups. Exposure of Wistar rats to Dichlorvos has no impact on haematological parameters in middle agerats. However, dichlorvos affects young and old animals proving age dependent effect of DDVP on hematological parameters.